Real world evidence of effectiveness and safety of an oral formulation containing un-denatured type-II collagen 40 mg and aflapin 100 mg (HAPID®) in the management of osteoarthritis of knee: findings of a prospective, multi-center, observational study - Pal, A. K.; Sen, Sanjoy; Behera, Sanatan; Anand, Rajeev; Bhattacharyya, Chandrachur; Kalidoss, K.; S., Arumugam; ., Shivarajaiah; Jagadeesh, P. C.; Karvir, Sagar; Patil, J. C.; Anand, Rajeev; et al. (International Journal of Research in Orthopaedics, 2022)
Background: Osteoarthritis (OA) of knee is a common progressive multifactorial joint disorder affecting the quality of life, and surgical repair is the final option which has substantial impact on healthcare costs. This real-world study evaluates the efficacy and safety of an oral formulation containing UC-II and aflapin (Boswellia serrata extract enriched in 3-O-acetyl-11-keto-beta-boswellic acid) for treatment of OA of knee. Methods: Data of 505 ambulatory adult patients (study duration-Jul-21 to Jul-22) of either gender (227 M, 278 F) having OA of knee, and who received study treatment (capsule HAPID®, Wockhardt, India) once daily for a period of up to 90 days were included for the study after obtaining informed written consent. Primary outcomes were mean change in Western Ontario and McMaster universities OA index (WOMAC) scores from baseline through day 90 (total and sub-scales for joint pain, joint stiffness, and physical function), and change in 0-10 visual analogue scale (VAS) score for pain. Results: About 285 (56.4%) patients were newly diagnosed, majority (63.4%) were having grade 2 severity of OA (Kellgren and Lawrence grade). The mean (SD) baseline total WOMAC scores improved from 60.94 (23.60) at baseline to 26.42 (22.19) on day 90. Significant improvements were seen starting from day 5 (p=0.023) and progressively up to day 90 (p<0.0001). Conclusions: The excellent safety and efficacy profile of combination therapy with aflapin and UC-II makes it a desirable pharmacological treatment modality for management of patients of knee OA.